AN OVERVIEW ON THE JUDICIAL MONITORING AND SUPERVISION URGENCY IN MAKING CLEAN JUDICIARY - Yulia Monita; Nys Arfa; Elizabeth Siregar (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
A clean judiciary is the hope of all levels of Indonesian society. A clean judiciary is a court that carries out its duties and functions based on the provisions of the applicable laws and prioritizes legal certainty, justice, and benefit. This study aims to see how regulating and changing forms of judicial supervision and warning in realizing clean justice and to answer whether other legal rules are still needed to strengthen the role of the people who participate in and monitor the judicial path. This research is normative legal research, it is a study that examines matters of a theoretical nature, principles, conceptions, legal doctrine, and legal principles related to judicial supervision and supervision in the context of realizing a clean judiciary. Meanwhile, the legal materials used are primary, secondary, and tertiary legal materials and their sources. The results of this research are a) judicial monitoring and supervision should be done in order to conduct a clean judiciary, b) monitoring and supervising are done not to intervening the results of courts decisions but as a measuring tool to what extent the decisions are fair to the society, c) there are still several judges' decisions which, according to society, are controversial, illustrating the public's distrust of the judiciary.